169k views
4 votes
Solve the system using the elimination method.

3x + 2y-z= 8
-3x + 4y + 5z = -14
X- 3y + 4z=-14

User Davebytes
by
6.5k points

1 Answer

6 votes

Answer:

Explanation:

3x + 2y - z = 8

-3x + 4y + 5z = -14

6y + 4z = -6

3x + 2y - z = 8

-3x + 9y - 12z = 42

11y - 13z = 50

6y + 4z = -6

66y - 78z = 300

-66y - 44z = 66

-122z = 366

z = -3

3x + 2y + 3 = 8

3x + 2y = 5

-3x + 4y -15 = -14

-3x + 4y = 1

3x + 2y = 5

-3x + 4y = 1

6y = 6

y = 1

3x + 2 + 3 = 8

3x + 5 = 8

3x = 3

x = 1

x=1, y = 1, z = -3